Direct supervisory adaptive fuzzy controller applied to pH control - Nazaruddin, Y.; Astrid, P.; Samyudia, Yudi (Institute of Electrical and Electronics Engineers Inc., 2015)
© 1999 EUCA. A design approach of a direct supervisory adaptive fuzzy controller applied to pH control of a neutralization process is presented in this paper. Structure and designs of the controller using this approach will be briefly discussed, which includes fuzzy controller comprising a number of fuzzy systems constructed from the control knowledge as well as a supervisory scheme which will monitor the systems performance during the operation. To improve the performance, two level quantization mechanism and an indication function were added in the controller design. Results of simulation studies show how the designed supervisory adaptive fuzzy controller achieved the desired performance. Observations were also made by comparing the solution with nonsupervisory scheme and non-adaptive fuzzy controller which uses pre-defined linguistic rules.